(untitled) (Orfeu, 2025)
This study explores the adaptation of Antonio Vivaldi’s Concerto RV 93, originally conceived composed for the lute, for performance on the Baroque guitar. Drawing on historical treatises such as those by Gaspar Sanz and Johann Mattheson, the research investigates interpretative practices of the Baroque period, with an emphasis on fingering and ornamentation techniques. The adaptation incorporates elements like re-entrant tuning, campanellas, and improvised ornamentation, showcasing the expressive and idiomatic richness of the Baroque guitar. The piece, preserved in its stylistic essence, gains a new sonic dimension, highlighting the performer’s role as part of the creative process. The bibliographic analysis demonstrates that this approach not only honors Baroque tradition but also expands the performative possibilities of the work, reaffirming the relevance of idiomatic interpretation and the interplay between theory and practice in music.